Maple Syrup Disease: Diagnosis and Therapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Infants at high risk for maple syrup disease (MSD) were identified by family history and molecular testing for the Y393N mutation of the E1a subunit of the branched chain a-ketoacid dehydrogenase in a study at Johns Hopkins University School of Medicine, Baltimore, MD.